2020
DOI: 10.3390/rs12050801
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Urban Land Surface Temperature Variations Under Zhengzhou City Expansion Using Landsat-Like Data

Abstract: Satellite-based remote sensing technologies are utilized extensively to investigate urban thermal environment under rapid urban expansion. Current Moderate Resolution Imaging Spectroradiometer (MODIS) data are, however, unable to adequately represent the spatially detailed information because of its relatively coarser spatial resolution, while Landsat data cannot explore the temporally continued analysis due to the lower temporal resolution. Combining MODIS and Landsat data, “Landsat-like” data were generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 76 publications
1
16
0
1
Order By: Relevance
“…Lin et al found that the area of BYD lake in flood season can reach 290 km 2[66], and it is difficult to achieve remote sensing inversion with a large range, a high frequency, and a high spatial resolution. Yang et al used STF for the inversion of surface temperature in Zhengzhou City[54], and we applied STF to the inversion of Chl-a with the same good results. A similar study was conducted by Liu et al who used Sentinel-2, Landsat-8, and Modis for spatio-temporal fusion and SPM (suspended particulate matter) inversion[67].…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…Lin et al found that the area of BYD lake in flood season can reach 290 km 2[66], and it is difficult to achieve remote sensing inversion with a large range, a high frequency, and a high spatial resolution. Yang et al used STF for the inversion of surface temperature in Zhengzhou City[54], and we applied STF to the inversion of Chl-a with the same good results. A similar study was conducted by Liu et al who used Sentinel-2, Landsat-8, and Modis for spatio-temporal fusion and SPM (suspended particulate matter) inversion[67].…”
mentioning
confidence: 84%
“…Finally, the GF2-like image at time T2 is fused and generated. The calculation process for step 5 is as follows [54]:…”
Section: Spatial and Temporal Fusion Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that although revisions of FSDAF, i.e., IFSDAF, SFSDAF, and FSDAF 2.0 have been proposed, the framework of these hybrid STF methods is basically consistent with the original FSDAF. Moreover, FSDAF has been widely used [63][64][65][66], suggesting its effectiveness and representativeness. We thus used FSDAF as the representative method of the hybrid STF methods.…”
Section: Comparison and Evaluation Strategymentioning
confidence: 99%
“…FSDAF is suitable for heterogeneous landscapes and can effectively capture land cover changes. In recent years, FSDAF has been used in a number of applications, such as monitoring dynamics of impervious surface [38], wetland [39], land surface temperature [40], and vegetation [41]. Moreover, FSDAF provides a framework for addressing both gradual and abrupt land-cover changes during the spatiotemporal fusion process.…”
Section: Introductionmentioning
confidence: 99%